CIRCULATING PROFILE OF ROTAVIRUS A, G AND P GENOTYPES BEFORE AND AFTER VACCINE INTRODUCTION IN THE BRAZILIAN MID-WEST 1986-2015 - Nunes Vieira Almeida, Tâmera; Teixeira de Sousa, Teresinha; Souza, Menira; Souza Fiaccadori, Fabíola; Rady Badr, Kareem; das Dôres de Paula Cardoso, Divina (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
The purpose of this study was to perform a comparative analysis of Rotavirus A (RVA) G and P genotypes circulating in the Brazilian Mid-West in the period 1986-2015. Seven studies conducted from 1986 to 2009 were included, as well as fecal samples obtained in the period 2014-2015. RVA was screened by ELISA and/or PAGE; genotyping by conventional RT-PCR and/or genomic sequencing. A temporal variation in the predominance of G genotypes mainly G1 and G2 with G9 and G12 emergence was observed. Even with vaccination, RVA continues to circulate in the population, requiring continuous virus monitoring.